Evaluation of the Clinical Efficacy of Prednisolone in the Treatment of Inflammatory Bowel Diseases with Different Dosage Methods - O. P. Alekseeva; S. V. Krishtopenko; A. A. Alekseeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Aim: to investigate the clinical efficacy of two methods of oral dosing of prednisolone (in mg and mg/kg) for the induction of remission for patients with ulcerative colitis (UC) and Crohn's disease (CD) using the technology of constructing and evaluating the effectiveness function (dose-effect relationship).Material and methods. In this study were included 86 patients aged from 18 to 65 years with moderate or severe active inflammatory bowel disease (61 — UC, 25 — CD). All patients were treated with prednisolone at an initial daily dose from 30 to 60 mg with a subsequent tapering of dose. The clinical response to treatment was evaluated at the time of complete withdrawal of prednisolone using the generally accepted criteria. Two efficiency functions were constructed, compared and analyzed: the first — at the initial dosage of prednisolone in mg and the second calculating the dose in mg/kg of patient weight. The patients' body weight ranged from 41 to 98 kg. The “dose-effect” relationship for prednisolone was constructed with statistical transformation of the baseline clinical data and a quantitative expression of the actual doses and alternative responses into a graph of the effectiveness function. The mean value at each point was estimated based on the regression kernel scoring method.Results. Two graphs of the “dose-effect” of prednisolone in mg and mg/kg of patient weight were constructed. The optimal clinically effective dose (OCED) when calculated in mg/kg of weight was 0.70 ± 0.01 (0.68 + 0.72) mg/kg with the corresponding effect 79.25 ± 6.26 (66.62 91.88) %. When two graphs in mg and mg / kg of weight were superimposed, it is shown that when an initial dose of 40 mg is prescribed without taking into account the patient's weight, the effect of therapy will be 25 % lower. Prescribing a dose of 60 mg per day without weight will be optimal for patients with a body weight of 85-90 kg. With a lower body weight, the clinical effect will not decrease, but the likelihood of recognized side effects of prednisolone should be expected in proportion to the decrease in body weight.Conclusion. The clinical efficacy of two methods of prednisolone dosing (mg and mg/kg) for patients with IBD during the first induction course was compared.Using a new technology for constructing and evaluating the effectiveness function (dose-effect relationship) allowed us to prove a reliable relationship between the body weight of patients with the clinical effect of prednisolone in patients with UC and CD. Based on the analysis of the dose-effect relationship, the optimal clinically effective dose of prednisolone for patients with UC and CD during the first induction course was established, equal to 0.70 mg/kg, which can be recommended for use in clinical practice for calculating individual doses.